Hőkezelési folyamat modellezési adatainak előkészítése, elemzése húskonzerv-gyártás gázfogyasztásának optimálásához - Fabulya, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
We have been looking for the possibility to build a computer model of costly gas utilization in the course of heat treatment of canned meat. This was necessary for us, as the first part of our long-term research, to be able to accomplish minimized costs by synchronizing heat treatment processes running side by side and by production programming to define completion time of the cans. First, because of our multiple data (paper based, text file, image file, Excel file), we have arranged them under a common user interface, while defining the best one from the data with different precision appearing in several sources. Based on the accurate data we did correlation and regression analysis to define the data influencing the gas consumption and to see whether our present data was enough to develop a model. Since the furnace has to ensure the steam supply of the heat treatment equipment and the heating of the buildings too, we defined the gas consumption of the furnace which is dependent on the environmental temperature.